DAMPAK PERUBAHAN IKLIM TERHADAP SEKTOR PERTANIAN PADI - Fatchur Rozci (Jurnal Ilmiah Sosio Agribis, 2023)
The phenomenon of greenhouse gases causes the impact of climate change which results in an increase in the earth's temperature. This research was conducted with the aim of knowing whether there are indications of climate change that is occurring, the amount of contribution of greenhouse gas emissions in the agricultural sector, the impact of climate change on the agricultural sector, to the efforts needed to deal with climate change in the agricultural sector using secondary data with qualitative research through literature review approach. The existence of indications of climate change is something that is common for farmers which is an obstacle in the agricultural sector. Climate change cannot be eliminated, but can be minimized by taking steps to anticipate and adapt to climate change. Most of the gas comes from microbial decomposition, burning of plant litter and soil organic matter. Climate change not only causes global warming and sea level rise, but also threatens food security because it can have a negative impact on the agricultural sector, especially crop loss. These adaptation activities include developing and accelerating the adoption of agricultural technologies that are more productive and more adaptive to climate change.Keywords : Climate Change, Agricultural, Impact, Greenhouse Gases, Farmers.